Hubungan Desa Wisata Terhadap Kesejahteraan Masyarakat: Suatu Penelitian Tentang Hubungan Desa Wisata Terhadap Kesejahteraan Masyarakat Di Desa Ngebel, Kecamatan Ngebel, Kabupaten Ponorogo Tahun 2021 - Dinda Aulia Putri Prafendia; Bambang Martin Baru; Harianto (JURNAL SOSIAL, 2024)
Tourism is part of economic development aimed at expanding employment opportunities and equalizing people's welfare. Currently, the tourism potential in Ponorogo has not been optimally developed, one of which is Ngebel Lake. Currently, the Ngbel village community, which used to be Ngbel Lake, is full of visitors. . The research aims to determine the relationship between rural tourism and community welfare in Ngebel Village, Ngebel District, Ponorogo Regency, in 2021. The type of research used in this research is quantitative with an explanatory type. The results of the study were obtained by distributing questionnaires to 70 respondents. The population in this study were the people of the Ngbel village and the managers of the Ngbel Lake. The sampling technique uses random sampling where all individuals in the independent population or groups are given the same opportunity to choose sample members. The reason for choosing a tourist object for research was because the ngebel tourist attraction became empty of visitors due to rising ticket prices and the access road to the lake being difficult and the dominant Ngbel village community working as traders around the lake being affected. From the results of the study it was found that the relationship between the two variables was STRONG with a result of 0.690 which stated the degree of strength of the relationship between the two variables was at 0.50-0.75. In this case, it can be interpreted that there is a tourism village relationship to the welfare of the people in Ngebel Village, Ngebel District, Ponorogo Regency, in 2021.